A moderate response to plasmapheresis in nephrogenic systemic fibrosis - Pelin Ustuner; Ozlem Karadag Kose; A. Tulin Gulec; Ozlem Ozen (Clinics and Practice, 2011)
Nephrogenic systemic fibrosis (NSF) is a recently identified idiopathic cutaneous fibrosing disorder that occurs in the setting of renal failure. The disease initially called nephrogenic fibrosing dermopathy is closely linked to exposure to gadolinium-based contrast media used during magnetic resonance imaging in patients with renal insufficiency. Although little is known about the pathogenesis of this disease, the increased expression of transforming growth factor-beta has been demonstrated recently. Herein, we present a case of NSF was partially treated due to a moderate and temporary response to plasmapheresis with no recurrence for 6 months, but returned at the end of 6th month.